Cognition and Society. Treatment Forms at the Dawn of Feudalism: Señor and the Honorific Formulas with -ísimo - Andrzej Zieliński (Verba Hispanica)
The objective of this study is to delve into the origin of two treatment formulas: señor, from senior “older”, and those with the superlative suffix. Both are very closely linked to the imposition of a new social model, feudalism, which is characterized by organizing itself on a vertical social scale, coinciding with the scale of quantification characteristic of degree expressions. In both acts the conceptual metaphor is more is up.